Penerapan Metode Balanced Scorecard dan Analytical Hierarcy Process (AHP) Dalam Penentuan Karyawan Berprestasi (Studi Kasus : Kantor Pertanahan Kota Pekanbaru) - Dega Aguansyah (Fakultas Teknik UMRI, 2020)
The National Land Agency (abbreviated BPN in Indonesian) is a non-ministerial government institution that is under and responsible to the President and led by the Head (in accordance with Presidential Decree No. 63 of 2013). The problems that occur at the Pekanbaru Land Office in determining outstanding employees are only seen based on the results of the work they do, not based on the criteria for each employee. Therefore, this study was conducted to provide application in determining outstanding employees with more detailed results based on the criteria of each employee using several methods, including the Balanced Scorecard method and the Analytical Hierarchy Process (AHP). Based on the research results, it is known that based on the Balanced Scorecard method, the criteria to be used are Comprehension, Accuracy, Craft, and Discipline with the same highest value, namely 12.25. After that, each employee was assessed based on the criteria using the Analytical Hierarchy Process (AHP) method with the highest score being DHEA with a value of 0.301.